2012
DOI: 10.1029/2011jd017069
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of evolving TRMM‐based multisatellite real‐time precipitation estimation methods and their impacts on hydrologic prediction in a high latitude basin

Abstract: [1] The real-time availability of satellite-derived precipitation estimates provides hydrologists an opportunity to improve current hydrologic prediction capability for medium to large river basins. Due to the availability of new satellite data and upgrades to the precipitation algorithms, the Tropical Rainfall Measuring Mission (TRMM) Multisatellite Precipitation Analysis real-time estimates (TMPA-RT) have been undergoing several important revisions over the past ten years. In this study, the changes of the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
102
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 147 publications
(105 citation statements)
references
References 70 publications
3
102
0
Order By: Relevance
“…The lower the RMSE and RB, the better the estimation. These comparison criteria have been used by many studies (Ebert et al, 2007;Wang et al, 2011;Yong et al, 2012), so they are used in this study. Probability distributions by occurrence and volume are also analysed, which can provide us with the information on the frequency and on the product error dependence on precipitation intensity (Chen et al, 2013a, b).…”
Section: Criteria For Accuracy Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The lower the RMSE and RB, the better the estimation. These comparison criteria have been used by many studies (Ebert et al, 2007;Wang et al, 2011;Yong et al, 2012), so they are used in this study. Probability distributions by occurrence and volume are also analysed, which can provide us with the information on the frequency and on the product error dependence on precipitation intensity (Chen et al, 2013a, b).…”
Section: Criteria For Accuracy Assessmentmentioning
confidence: 99%
“…WEB-DHM has been used in several evaluations and applications (Wang et al, 2010a(Wang et al, , b, 2012Shrestha et al, 2014). WEB-DHM input data include precipitation, temperature, downward solar radiation, long-wave radiation, air pressure, wind speed, and humidity.…”
Section: Web-dhmmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have been carried out to evaluate the suitability of a number of satellite-based precipitation estimate products in forcing hydrologic models and simulating streamflow for various regions around the world (e.g., Yilmaz et al, 2005;Artan et al, 2007;Su et al, 2011;Bitew et al, 2012;Yong et al, 2012, Yang et al, 2015. However, there are few evaluation studies focusing on hydrological modeling driven by satellite rainfall products on the Tibetan Plateau.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated the utility of TRMM datasets in estimating rainfall for hydrological modelling of medium-sized and large catchments (e.g. Hong et al 2007;Su et al 2008;Nikolopoulos et al 2013;Yong et al 2012). Less testing has been undertaken in smaller catchments (less than 100 km 2 ).…”
Section: Rainfall Data and Spatial Modellingmentioning
confidence: 99%